2014
DOI: 10.1016/j.cmet.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Hif-2α Promotes Degradation of Mammalian Peroxisomes by Selective Autophagy

Abstract: Peroxisomes play a central role in lipid metabolism, and their function depends on molecular oxygen. Low oxygen tension or von Hippel-Lindau (Vhl) tumor suppressor loss is known to stabilize hypoxia-inducible factors alpha (Hif-1α and Hif-2α) to mediate adaptive responses, but it remains unknown if peroxisome homeostasis and metabolism are interconnected with Hif-α signaling. By studying liver-specific Vhl, Vhl/Hif1α, and Vhl/Hif2α knockout mice, we demonstrate a regulatory function of Hif-2α signaling on pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 46 publications
7
162
0
1
Order By: Relevance
“…51,52 Previous studies have shown that HIF1A contributes to autophagy regulation in hypoxia. 20,[24][25][26][27][68][69][70] The BH3 domains of BNIP3 and BNIP3L, known HIF1A targets, disrupt the BCL2-BECN1 complex, releasing more BECN1 to be involved in the autophagic process. 24 In NP cells, although the BNIP3 level was increased under hypoxia, the absence of a concomitant increase in p-BECN1 Ser93 indicated a possible lack of correlation with autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Previous studies have shown that HIF1A contributes to autophagy regulation in hypoxia. 20,[24][25][26][27][68][69][70] The BH3 domains of BNIP3 and BNIP3L, known HIF1A targets, disrupt the BCL2-BECN1 complex, releasing more BECN1 to be involved in the autophagic process. 24 In NP cells, although the BNIP3 level was increased under hypoxia, the absence of a concomitant increase in p-BECN1 Ser93 indicated a possible lack of correlation with autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α activation as a result of VHL loss or pseudohypoxia contributes also to the development of the Warburg effect. Furthermore, although the shift from oxidative phosphorylation to glycolysis is attributed to the activity of HIF-1α, at least in the liver HIF-2α induces the same genes involved in this metabolic adaptation (Rankin et al, 2009;Walter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial protein levels are similar in control and knockout livers (Walter et al, 2014), suggesting that constitutive HIF-α signaling does not affect hepatic mitochondrial mass. However, subcellular fractionation of livers from control and Vhl −/− mice shows that mitochondrial protein levels are decreased in the heavy mitochondrial fraction of Vhl −/− livers compared with controls, whereas their levels are increased in the light mitochondrial fraction (Walter et al, 2014). Further purification of the light mitochondrial fraction by density gradient centrifugation and immunoblots of gradient fractions show that the OMM protein VDAC shifts toward lower density fractions.…”
Section: Hepatic Hif-α Signaling and Mitochondrial Abundancementioning
confidence: 92%
See 2 more Smart Citations